(untitled) (Research, Society and Development, 2020)
The objective was to evaluate the production process of polymer-fiber composites, by means of pressing, using low density polyethylene (LDPE) reinforced with wood flour in two granulometries and coconut fibers. The physical and mechanical properties of the molds produced were evaluated. In the process, it was used as a LDPE matrix in a virgin and recycled mixture reinforced with “thick” pine wood flour obtained in forestry industries in the city of Irati-PR, “fine” pine wood flour and coconut fiber provided by Inbrasfarma Ltda. The LDPE was mixed with each reinforcement, together with a coupling agent (Polybond 3009), and the mixtures were then processed using a twin screw extruder. The mixture was molded by compression, resulting in a series of pressed specimens, which were subjected to tensile, bending and hardness tests. The evaluation of the results showed that the addition of wood reinforcement to plastic, in general, increased the mechanical properties of the composite while the coconut fiber reinforcement was favorable only to flexion. There were significant differences in the properties of the composites due to the studied compositions.